2012
DOI: 10.1590/s0104-530x2012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Evolução da literatura de inovação em relações de cooperação: um estudo bibliométrico num período de vinte anos

Abstract: Uma das principais características das relações de interação em busca de cooperação consiste na busca de novas formas de gestão produtiva e administrativa, condicionadas pela pressão por inovação. O objetivo deste trabalho é realizar uma análise da literatura, entre os anos de 1991 e 2010, sobre os temas inovação e cooperação. Para isso, os autores utilizaram o método de estudo bibliométrico e análise qualitativa de alguns dos trabalhos e referências. Foi realizada uma busca na base de dados ISI Web of Knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
0
5
0
11
Order By: Relevance
“…Radnor et al 2012, despite being one of the most cited articles, with 112 citations, is not in a prominent position, unlike Mazzocato et al (2010), with the same number of citations (112). One possible explanation for The degree of intermediation corresponds to how much an article acts as a facilitator of integration with other articles (Lopes & Carvalho, 2012), it shows how an author is connected with other authors in the network, attributing the importance that this author has in a specific flow of information, characterizing the shortest path possible between the authors (Bordin et al, 2014). This means that the greater degree of betweenness, the more works cited by the related authors, making the cited work become a reference among references.…”
Section: Resultsmentioning
confidence: 99%
“…Radnor et al 2012, despite being one of the most cited articles, with 112 citations, is not in a prominent position, unlike Mazzocato et al (2010), with the same number of citations (112). One possible explanation for The degree of intermediation corresponds to how much an article acts as a facilitator of integration with other articles (Lopes & Carvalho, 2012), it shows how an author is connected with other authors in the network, attributing the importance that this author has in a specific flow of information, characterizing the shortest path possible between the authors (Bordin et al, 2014). This means that the greater degree of betweenness, the more works cited by the related authors, making the cited work become a reference among references.…”
Section: Resultsmentioning
confidence: 99%
“…The research was carried out using the ISI Web of Science and Scopus databases based on their relevance to the academic community since both databases hold the largest amounts of publications, have filters for document types and solely articles as well as including only journals with double blind peer review during the submission processes (Carvalho et al, 2013;Lopes & Carvalho, 2012;Watanuki et al, 2014). A synthesis of the research process and filters adopted by both databases are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…For Leem & Chun (2014), the centrality degree of an article suggests that the more connections a node has, the more central this article is or, in other words, centrality is defined as the number of interactions a node has with others (Ting & Tsang, 2013). Betweenness degree is the degree of an article as enabler of the intermediation between other articles (Lopes & Carvalho, 2012). According to Bordin et al (2014), betweenness degree is understood as how connected an author is with other authors in the network attributing the importance an author has when the information flux that goes through it is considered, in the interconnection between two other authors in the same network, always characterizing the shortest path possible.…”
Section: Citations and Network Analysismentioning
confidence: 99%
“…http://www.ijmp.jor.br v. 9, n. 2, April -June 2018 ISSN: 2236-269X DOI: 10.14807/ijmp.v9i2.754 matter (DENYER;TRANFIELD, 2009). The analysis of the research is characterized as theoretical-conceptual and objective to present the main reference models that contextualize the PDP with the purpose of analyzing its methodological classifications (LOPES; CARVALHO, 2012).…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%